Beach ridges as paleoseismic indicators of abrupt coastal subsidence during subduction zone earthquakes, and implications for Alaska-Aleutian subduction zone paleoseismology, southeast coast of the Kenai Peninsula, Alaska - Kelsey, Harvey M.; Witter, Robert C.; Engelhart, Simon E.; Briggs, Richard; Nelson, Alan; Haeussler, Peter; Corbett, D. Reide (Megathrust Earthquakes and Sea-level Change: a Tribute to George Plafker, 2015)
The Kenai section of the eastern Alaska-Aleutian subduction zone straddles two areas of high slip in the 1964 great Alaska earthquake and is the least studied of the three megathrust segments (Kodiak, Kenai, Prince William Sound) that ruptured in 1964. Investigation of two coastal sites in the eastern part of the Kenai segment, on the southeast coast of the Kenai Peninsula, identified evidence for two subduction zone earthquakes that predate the 1964 earthquake. Both coastal sites provide paleoseismic data through inferred coseismic subsidence of wetlands and associated subsidence-induced erosion of beach ridges. At Verdant Cove, paleo-beach ridges record the paleoseismic history; whereas at Quicksand Cove, buried soils in drowned coastal wetlands are the primary indicators of paleoearthquake occurrence and age. The timing of submergence and death of trees mark the oldest earthquake at Verdant Cove that is consistent with the age of a well documented ∼900-year-ago subduction zone earthquake that ruptured the Prince William Sound segment of the megathrust to the east and the Kodiak segment to the west. Soils buried within the last 400–450 years mark the penultimate earthquake on the southeast coast of the Kenai Peninsula. The penultimate earthquake probably occurred before AD 1840 from its absence in Russian historical accounts. The penultimate subduction zone earthquake on the Kenai segment did not rupture in conjunction with the Prince William Sound to the northeast. Therefore the Kenai segment, which is presently creeping, can rupture independently of the adjacent Prince William Sound segment that is presently locked.